Separation of sedimentary phytoliths from other biogenic silica particles for triple oxygen isotope analysis - Charlotte Mention; Julie C. Aleman; Jean-Charles Mazur; Yannick Garcin; Christelle Hély; Anne Alexandre (MethodsX)
Phytoliths are amorphous silica particles that precipitate within and between plant cells, and their fossilized morphological assemblages are widely used to reconstruct paleo-vegetation. The triple oxygen isotope composition of phytoliths, expressed by the 17O-excess, is a promising proxy to reconstruct atmospheric relative humidity (RH). However, fossil phytoliths in lake or peat sediments often coexist with diatom frustules and sponge spicules, whose oxygen isotope signatures contribute to the average isotopic composition of biogenic silica, biasing the RH reconstruction. In this case, it is necessary to separate or at least concentrate the phytoliths. We developed a filtration protocol for this purpose. We tested the protocol on 31 lacustrine and peat sedimentary samples from West and Central Africa, and these are the main results: • Phytolith concentrations increased in 23 samples, primarily due to the removal of long pennate diatom frustules and sponge spicules. Six samples showed no significant change in phytolith concentration, while two samples showed a decrease. • Twenty-nine samples achieved final phytolith proportions exceeding 40 % and a sensitivity analysis based on an isotope mass balance equation confirmed that these samples are suitable for 17O-excess measurements to reconstruct RH.